2019
DOI: 10.1177/0957650919855911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of large eddy simulation and Reynolds-averaged Navier–Stokes evaluations with experimental tests on U-bend duct geometry

Abstract: The correct prediction of the flow field is of crucial importance to drive numerical optimization to a real improvement of a design. For this purpose, different numerical approaches can be used to study the fluid dynamics characteristics and the performance of the design. In particular, in the present work the Reynolds-averaged Navier–Stokes and large eddy simulation approach are compared for an internal aerodynamic application. The obtained solutions are validated against experiments through a quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…However height and length of the separation region are underestimated. Similar behavior is also noted in the RANS-based results of Alessi et al [2]. Figure 10 shows a good match between STAMPS and LES for the counter-rotating Dean vortices at the 90 • turn region, only small discrepancies near the inner wall separation region can be observed.…”
Section: Cfd Solver Validationsupporting
confidence: 81%
See 2 more Smart Citations
“…However height and length of the separation region are underestimated. Similar behavior is also noted in the RANS-based results of Alessi et al [2]. Figure 10 shows a good match between STAMPS and LES for the counter-rotating Dean vortices at the 90 • turn region, only small discrepancies near the inner wall separation region can be observed.…”
Section: Cfd Solver Validationsupporting
confidence: 81%
“…6b. The comparison of the simulated velocity field and experimental results by Coletti et al [6], the Large Eddy Simulation results by Alessi et al [2] and the STAMPS results is shown in Fig. 9 for the symmetric mid plane (Z/D h ).…”
Section: Cfd Solver Validationmentioning
confidence: 92%
See 1 more Smart Citation
“…The same behaviour is highlighted on the outer-wall at the end of the bend. Similar conclusions can be drawn for the comparison of the initial geometry [40].…”
Section: The U-bend Test Casesupporting
confidence: 81%
“…However, a recirculation bubble, not detected by the RANS evaluation, is still present inside the design as revealed by the experimental validation through Particle Image Velocimetry (PIV) [39]. On the other hand, simulations using LES could replicate with high accuracy the experimental findings [40]. To further improve the U-bend design, a LES based approach is thus inevitable.…”
Section: Introductionmentioning
confidence: 99%